Criminalization of Unregistered Marriage in Indonesia: A Legal System Analysis Based on Friedman's Theory - Rosyadi, Imron; Fuad, Helmy Ziaul; Zaimuddin, Ashlaha Baladina (Universitas Islam Negeri Raden Intan Lampung, 2025)
This article examines the criminal provisions stipulated in Chapter IX, Article 45 of Government Regulation No. 9 of 1975, concerning the Implementation of Law No. 1 of 1974 on Marriage, using the three elements of Lawrence M. Friedman's legal system: Legal Substance, Legal Structure, and Legal Culture. The research method combines a literature review with descriptive normative legal research. This study identifies the high rate of unregistered marriages in Indonesia, which contrasts with the decline in official marriages, reflecting the ineffectiveness of Article 45 of Government Regulation No. 9 of 1975 in enforcing criminal sanctions. Analysis of the Lawrence Legal System reveals that the substance of the law is flawed because criminalization is regulated through derivative regulations, contrary to the principle of nullum crimen sine lege. Institutionally, the Office of Religious Affairs (KUA) and the Civil Registry Office need to strengthen their functions, supported by consistent law enforcement by professional officials. Meanwhile, the low public awareness of marriage registration requires inclusive policies that integrate cultural approaches and context-based education. These findings contribute theoretically to the development of understanding regarding the effectiveness of criminal law enforcement in the context of marriage law while also suggesting the need for more decisive and comprehensive policy reforms to improve the implementation of the law and public legal awareness in practice